Management and utilization of reading areas of selected classes in the U.P. CDC - Cruda, Magan Arielle Mari C.C.; Dado, Denise Meghan A.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This paper described the management and utilization of homogenuous classes in the U.P. CDC. Interviews conducted with the teachers and creation of floor plans of each classroom showed the management aspect while observations of the classes served as the basis for utilization. The interviews discussed the management approaches used by the teachers to determine classroom arrangement, size allocation for the Reading Area, provision of furniture and other materials in the Reading Area, and rules implemented. Floor plans then provided supplementary visuals of the layout and structure of the classrooms. Anecdotes from the Infant Development Program, Toddlers, 2s, 3s, 4s, and 5s Class were then collated and categorized into four main themes play activity, book exploration, storytelling, and other activities. Results showed that both management and utilization are determined by the different age groups, as signified by their respective classes. Determined by each age groups developmental needs and interests, teachers are able to modify and adjust Reading Areas to accommodate the children. The use of the Reading Area, similarly, is based on the skills, abilities, and interests of the children. Recommendations include the enhancement of physical conditions such as its lighting to allow children to explore the books with ease. Similarly, since the Reading Area is not simply used for reading activities, play should be made a valid Reading Area activity with the provision of rules to maintain the areas calm and relaxing mood.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Classroom management -- Philippines